Von Willebrand’s Disease caused by Compound Heterozygosity for a Substitution Mutation (T1156M) in the D3 Domain of the Von Willebrand Factor and a Stop Mutation (Q2470X) - Lethagen, Stefan; Isaksson, Christina; Schaedel, Charlotta; Holmberg, Lars (Thrombosis and Haemostasis, 2002)
Hereditary defects of the von Willebrand factor (VWF) gene cause von Willebrand’s disease (VWD) which shows great variability dependent on the nature and location of the mutation. We here describe the characteristics of a substitution of methionine for threonine 1156 in the D3 domain of the VWF, i.e. the domain involved in the intracellular multimerization of pro-VWF dimers. A VWD patient with severe symptoms was a compound heterozygote for the T1156M mutation and a null allele (Q2470X) on the other chromosome. This led to marked reduction of plasma VWF concentration to about 0.05 U/ml and an abnormality of VWF multimers as in type 2A VWD. Expression in vitro of the mutation demonstrated that 1156M-VWF is secreted from COS-7 cells in a much reduced amount and lacking large multimers. When coexpressed with normal VWF 1156M-VWF decreased the secretion of normal VWF in a dose-dependent manner, the secreted VWF showing all the multimers. Two relatives of the propositus were single heterozygotes for the T1156M mutation and were either asymptomatic or had the manifestations of mild type 1 VWD. The expression data and studies of platelet VWF indicate that the T1156M mutation results in intracellular retention of VWF rather than impaired synthesis. Three other members of the family were heterozygotes for the Q2470X mutation and demonstrated the variable expressivity of a null allele.
Keywords: Von Willebrand’s disease; mutation; COS-7 cell transfection